(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
Pumpkin (Cucurbita pepo) is a member of the family Cucurbitaceae and its fruit parts are edible. This study evaluated the physicochemical properties of extracted oil from the seed of pumpkin. The results revealed a percentage yield of 41.08 ± 2.33, refractive index of 1.47 ± 0.18, relative density of 0.09 ± 0.02 g/cm3; saponification value of 184.60 ±1.67 mg/KOH/g, Acid value of 2.64 ±1.31 mgKOH/g, iodine value of 80.27±2.09 g of I2/100 g, and peroxide value of 11.0 ±1.0 mEq/Kg. The result shows that pumpkin seed oil may find application either in food industry as food addictive as it may pose a good quality shelf life or energy generation as biofuels.